STRENGTHENING THE PROFILE OF PANCASILA STUDENTS THROUGH PROJECT-BASED LEARNING IN LEARNING HISTORY - Nina Ariani Shofa (Universitas Muhammadiyah Semarang, 2021)
The Pancasila Student Profile strengthening project provides an opportunity for students to “experience knowledge” as a process of character building as well as an opportunity to learn from the environment. This research was carried out in the history lesson of phase E, class 10 Muhammadiyah Vocational School Kudus, with lessons on ” through making replicas. The character building taught to students are mutual cooperation (gotong royong), Critical thinking, and creative competence. Lesson study is used to project and capture signals from students in learning in order to provide recommendations for teachers to student needs and interpret student responses as potential that can be developed. Learning uses a project-based learning approach with products in the form of replicas of stone age culture. Students are given the opportunity to collaborate and create a product which is then presented in their language. It is clear that students demonstrate mutual cooperation competence in the process of making replicas, demonstrate Critical thinking competence by connecting materials and information related to the product to be made, and demonstrate creative competence because they have been able to make replicas made of plasticine from stone age culture. The conclusion of the analysis of the Pancasila student profile through the application of project-based learning is 1) each student's behaviour is a picture of potential that can be developed. 2) the choice of approach in learning is able to become a scaffolding in planting the dimensions of the Pancasila student profile. Keywords : Pancasila Students Profile, Project-based Learning, History